Spectacular improvement in vitamin D status in elderly osteoporotic women: 8-year analysis of an osteoporotic population treated in a dedicated fracture liaison service. Issue 12 (December 2015) - Amouzougan, A.; Deygat, A.; Trombert, B.; Constant, E.; Denarié, D.; Marotte, H.; Thomas, T.
Abstract Summary In a population of postmenopausal women with a fragility fracture, we found a drastic reduction in the proportion of women with severe (<25 nmol/L) and moderate (25 to 75 nmol/L) hypovitaminosis D, especially from 2009 onwards. These results show that supplementation has been very widely integrated into current practice. Introduction Vitamin D (25(OH)D) is essential for bone health. In institutionalised osteoporotic women, it reduces the risk of fragility fractures. Numerous articles suggesting the possibility of extraosseous effects have generated a growing number of publications and recommendations on more widespread administration, to limit the risks of moderate or severe hypovitaminosis D. We assessed the impact on clinical practice of these recommendations concerning 25(OH)D supplementation in elderly at-risk populations. Methods A total of 1486 postmenopausal osteoporotic women were seen in the context of a fracture liaison service (i.e. a rheumatology consultation following a peripheral fragility fracture), between May 2005 and December 2012. Of these, 1107 had a 25(OH)D assay (femur, n = 520; humerus, n = 207; wrist, n = 380). Results The average age of the total population was 76.7 ± 9.9 years, while for women with an available 25(OH)D assay, the average age was 75.1 ± 11.8 years. The average 25(OH)D (nmol/L) level was similar for the three fracture sites: femur, 30 ± 36.2; humerus, 27.5 ± 24; and wrist, 31 ± 26. A drastic reduction in the proportion of women with severe (<25 nmol/L) and moderate (25 to 75 nmol/L) hypovitaminosis D was observed, especially from 2009 onwards, with a mean prevalence of 69 and 30 % respectively before that year and 35 and 52 % thereafter. Conversely, the proportion of women with 25(OH)D at the threshold value of 75 nmol/L increased from 1.2 to 24 %. Overall, mean serum 25(OH)D levels were significantly higher when comparing the two periods 2005–2008 and 2009–1012 (17.6 ± 14.6 and 48.4 ± 39.2 nmol/L, respectively;p < 0.0001). Conclusion These results show that supplementation has been very widely integrated into current practice. We can expect it to yield beneficial effects in osseous and extraosseous terms in osteoporotic women, particularly the very elderly.